P166 "LONG QT SYNDROME:AN ENTIRE FAMILY WITH KCNQ1 MUTATION". (18th May 2022) - Di Domenico, A; De Carolis, B; De Raffele, M; Vitali, F; Balla, C
Abstract: Introduction: Congenital long QT syndrome (LQTS) is characterized by prolongation of the QT interval that can trigger life–threatening arrhythmias leading to syncope and sudden death. Mutations in genes encoding for ion channels have been identified in 75% of LQTS cases. Long QT syndrome type 1 (LQTS1) is one of three subtypes of LQTS identified based on genetic substrate. LQTS1 is linked to a "loss–of–function" mutation in the gene encoding the potassium channel KCNQ1, and arrhythmias tend to occur during childhood with prevalence in the male sex. Adrenergic triggers are the most important trigger for arrhythmic events. Clinical Case: Extensive family with long QT syndrome with positive genetics for mutation in the KCNQ1 gene. The index case in the family appears to be a woman who at the age of approximately 30 years died suddenly after surgery. The first patient subjected to genetic analysis, with positive result, was the daughter of this woman who, at the age of about 25 years has experienced a ventricular arrhythmia during induction of anesthesia for surgery with baseline ECG finding of prolonged QTc. Set beta–blocker therapy, arrhythmias no longer occurred. Subsequently, a cardiological screening including electrocardiogram, transthoracic echocardiography and genetic analysis was undertaken in first–degree relatives and, in cases of positivity, this screening was progressively extended to second–, third– and fourth–degree relatives. All the women in the family analyzed, eight in total, including two girls aged 5 and 12 years, tested positive for genetic analysis, and one of the women had a syncopal episode at the age of 50 years. Of the men analyzed, four in total, only two (father and son) tested positive on genetic analysis. In all patients with positive genetics a QTc >480 msec was detected on ECG in clinostatism and/or orthostatism, for which a diagnosis of LQTS1 (mean Schwartz–score 4) was made and beta–blocker therapy was started. Conclusions: This clinical case describes an entire family with LQTS with positive genetics for KCNQ1 with phenotypic manifestations different from those described in the literature, in particular with prevalence in the female sex and with onset of arrhythmias in adulthood.